Nilai-Nilai Islam dalam Tradisi Adat Budaya Suku Alas di Kabupaten Aceh Tenggara - Pinem, Radiyah Hanum; Batubara, Abdul Karim; Ali, M. Nasihudin (Warisan: Journal of History and Cultural Heritage, 2023)
This research was conducted to find out the Islamic values in the cultural traditions of the Alas tribe in Southeast Aceh district. It aims to find out the history of the early entry of Islam in the Alas tribe, Islamic values in the customary traditions of the Alas tribe, and the social order in the life of the Alas tribe. The type of research conducted uses descriptive qualitative methods of analysis, with an ethnographic approach.Â  The analysis technique used is good data collection that can be obtained with data through the implementation of observations and interviews. Overall, this research raises theoretical implications, namely the existence of cultural fusion, multicultural communication contained in social situations, as well as Islamic religious values in every traditional ceremony of the people of Southeast Aceh district. The role of Islamic values in fact has an influence on the social and cultural situation of the people in Southeast Aceh district. The three aspects (social, cultural, and Islamic) in the Southeast Aceh district can be said to be Local Wisdom. So that Islamic values in the Southeast Aceh region are able to influence the culture and social of the local community, thus creating Islamic culture and customs.